To believe, or not to believe?; that is the question a look into the experience a becoming an atheist. - Bernadas, Frances C. (Frances C. Bernadas, 2018)
"God is not necessary to be a good human."- Philippine Atheists and Agnostic Society. Atheists are one of the minorities in the world, but not much is known on how they achieve their atheist identity in the context of a religious country like the Philippines. This study utilized a phenomenological approach to examine the question, "What are the lived experiences of becoming an atheist?" The lived experiences of 6 male self-identified atheists (aged 18 to 26) were captured through semi-structured interviews. The findings indicated the four phases of becoming an atheist: questioning, confirming one's doubts, active rejection, and established atheist. However, atheists engage in selective disclosure which enabled them to not experience stigma and discrimination because of their atheist identity. Theoretical and practical implications are also considered on how the society can be more understanding and to eliminate the stigma tied with atheists.